2021
DOI: 10.1590/1518-8345.4668.3416
|View full text |Cite
|
Sign up to set email alerts
|

The use of antimicrobial-impregnated fabrics in health services: an integrative review

Abstract: Objective: to analyze evidence concerning the feasibility of antimicrobial-impregnated fabrics in preventing and controlling microbial transmission in health services. Method: an integrative review using the following databases: MEDLINE (via PubMed), Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, and Latin American and Caribbean Health Sciences Literature (LILACS), regardless of language and date of publication. Seven studies were included in the analysis to verify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Thus, the importance of HAI prevention in pediatric hospitalization units in the current global context of the new coronavirus pandemic is highlighted, considering, as already explained in the literature, its ability for transmission through indirect contact with surfaces in the environment or with objects used in the infected person and the susceptibility of infection by the virus in all age groups. 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the importance of HAI prevention in pediatric hospitalization units in the current global context of the new coronavirus pandemic is highlighted, considering, as already explained in the literature, its ability for transmission through indirect contact with surfaces in the environment or with objects used in the infected person and the susceptibility of infection by the virus in all age groups. 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…30 Thus, the importance of HAI prevention in pediatric hospitalization units in the current global context of the new coronavirus pandemic is highlighted, considering, as already explained in the literature, its ability for transmission through indirect contact with surfaces in the environment or with objects used in the infected person and the susceptibility of infection by the virus in all age groups. 31,34 As for the limitations of this study, the analysis and assessment of the effectiveness of SCD is only verified in one health institution and in a limited period of time. The difficulty comparing the data with other studies is also related to the type of methods used to analyze the surfaces, the C&D protocols, and the products used in other health services.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an extensive review of the related literature concluded that antimicrobial coatings applied to bed and bath linens and patient clothing showed some promise in reducing microbes on these surfaces, although no definitive efficacy was detected in reducing microbes when applied to healthcare workers' uniforms (Schneider et al, 2021). A gap in the literature exists when explaining why antimicrobial coatings on fabrics are effective in in vitro (laboratory) environments but are not effective in in vivo (hospital) environments, which we address in this study.…”
Section: Introductionmentioning
confidence: 99%
“…This proactive monitoring enables early detection of health issues and a timely intervention. Nevertheless, the looming perils of infectious diseases have accentuated the beneficial influence of antibacterial textiles in mitigating the proliferation of such outbreaks . However, the proliferation of bacterial contaminants may potentially undermine wearable textiles’ efficacy.…”
Section: Introductionmentioning
confidence: 99%